Value Added Analysis of Palm Sugar and Factors that Influence - Shofia Nur Awami; Sri Wahyuningsih (Jurnal Ilmiah ESAI, 2015)
Kendal Regency as the one regency in the Central Java Province has prospect for development of palm sugar small business. This research aimed to determine the amount of income, added value processing of palm sugar small bussiness, and to analyze the factors that influenced added value of of palm sugar small bussiness in Kendal Regency. This study use a purposive sampling  method. The location, beside Temanggung Regency and Klaten Regency, Kendal Regency is one of palm sugar centre in the Central Java Propince.  The average total production of palm sugar in  Singorojo District is 6,59 kilogram per production period. The processing of palm sugar production give added value  at Rp.2.758,- per liter. The average total production of palm sugar in  Limbangan District is 8,05 kilogram per production period. The processing of palm sugar production give added value  at is Rp.2.890,- per liter. Average net income per month in Kendal Regency is Rp. 2.167.377,-, with average revenue is Rp. 2.893.587,-. Added value of processed palm sugar in Kendal Regency were influenced by several factors including; the amount of labour, the producer’s age, raw material prices, output prices, and production capacity. Keywords: Added value, income, palm sugar